2022
DOI: 10.17085/apm.21044
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal tube cuff pressure during laparoscopic bariatric surgery: highs and lows

Abstract: Background: Gastric calibration tubes (GCTs) are a unique component of bariatric surgery. This study aimed to assess changes in the endotracheal tube (ETT) cuff pressure during laparoscopic bariatric surgery.Methods: This was a prospective observational study consisting of 124 American Society of Anesthesiologists class I–III morbidly obese patients (body mass index > 40 kg/m2) undergoing elective laparoscopic bariatric surgery under general anesthesia. The baseline ETT cuff pressure was 28 cmH2O. Cuff pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The results of this study showed that the ETCP varies significantly during this surgery. So that this pressure was significantly reduced during the removal of gastric calibration tubes (GCTs) and the release of the carbo peritoneum [ 17 ]. Also, the results of the study by Athiraman et al (2015), in which they examined cuff pressure changes with position change in patients undergoing neurologic surgery, showed that cuff pressure decreased significantly over time [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the ETCP varies significantly during this surgery. So that this pressure was significantly reduced during the removal of gastric calibration tubes (GCTs) and the release of the carbo peritoneum [ 17 ]. Also, the results of the study by Athiraman et al (2015), in which they examined cuff pressure changes with position change in patients undergoing neurologic surgery, showed that cuff pressure decreased significantly over time [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, an endotracheal tube cuff pressure of 20–30 cmH 2 O is recommended to create an adequate seal between the tube and trachea (Ferreira et al., 2021 ; Saxena et al., 2022 ; Wang et al., 2021 ). However, several studies have revealed that a cuff pressure of >30 cmH 2 O is required for some patients during mechanical ventilation (Nseir et al., 2009 ; Peters & Hoogerwerf, 2013 ; Rosero et al., 2018 ; Wu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, an endotracheal tube cuff pressure of 20-30 cmH 2 O is recommended to create an adequate seal between the tube and trachea (Ferreira et al, 2021;Saxena et al, 2022;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%